Efektivitas Media Papan Pintar Pada Pembelajaran Perubahan Wujud Benda Terhadap Keterlibatan Dan Minat Belajar Siswa SMP - Sari, Meirita; Hasanah, Qomariah; Zulkarnain, Zulkarnain; Pansuri, Hamzah (BALE LITERASI, 2026)
Science education at the elementary level has an important role in forming students' understanding of natural phenomena and basic concepts, one of which is changes in the state of objects which include the processes of melting, freezing, evaporation and condensation. This research aims to explore the effectiveness of using image media in smart board games as a learning aid to teach students changes in the shape of objects. This research was carried out at Smp IT Khairunnas, Bengkulu City, involving 30 class 7A students. The method used is descriptive qualitative with observation techniques and data collection through questionnaires distributed online. The research results show that using a smart board with image media can increase students' understanding of changes in the form of objects, as well as increase their involvement and interest in learning. This research concludes that smart board media is effective in strengthening students' understanding of the concept of changes in the form of objects and increasing a fun and interactive learning experience